2011
DOI: 10.3892/ijo.2011.1139
|View full text |Cite
|
Sign up to set email alerts
|

Model examinatio�n of chemoprevention with retinoids in squamous cell carcinomas of the head and neck region and suitable biomarkers for chemoprevention

Abstract: Abstract.The prognosis for patients with head and neck tumors (HNSCC) is poor, due among other things to the high-risk factor for locoregional recurrence and/or second primary tumors. Extensive studies on chemoprevention of oral pre-cancers to stop carcinogenesis and to prevent recurrence and/or second primary tumors have failed to reach the desired effects.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 101 publications
0
3
0
Order By: Relevance
“…It should be emphasized that most breast carcinomas and breast cancer cell lines show loss or down-regulation of RARβ receptor expression, whereas RARα and γ, as well as RXRs, appear to be variably expressed in both normal and tumor cells [220]. Expression of RARβ could be modulated by chemopreventive intervention [221,222] and may therefore serve as an intermediate biomarker in chemoprevention trials for some cancers [223]. Provitamin A carotenoids, such as β-carotene and its excentric cleavage metabolites, can serve as direct precursors for (all- trans )-retinoic acid and (9- cis )-retinoic acid which are ligands for RAR and RXR, respectively.…”
Section: Mechanisms Of Cancer Chemoprevention By Carotenoidsmentioning
confidence: 99%
“…It should be emphasized that most breast carcinomas and breast cancer cell lines show loss or down-regulation of RARβ receptor expression, whereas RARα and γ, as well as RXRs, appear to be variably expressed in both normal and tumor cells [220]. Expression of RARβ could be modulated by chemopreventive intervention [221,222] and may therefore serve as an intermediate biomarker in chemoprevention trials for some cancers [223]. Provitamin A carotenoids, such as β-carotene and its excentric cleavage metabolites, can serve as direct precursors for (all- trans )-retinoic acid and (9- cis )-retinoic acid which are ligands for RAR and RXR, respectively.…”
Section: Mechanisms Of Cancer Chemoprevention By Carotenoidsmentioning
confidence: 99%
“…All-trans retinoic acid (ATRA) therapy has been successfully used for chemoprevention of SCCs in several studies. [21][22][23] In a recent trial, Cheepala and colleagues compared the gene expression profiles of control skin to skin exposed to ATRA and concluded that ATRA's mechanism involves targeting the BRAF signaling pathway. 22 This patient's lesions improved after starting isotretinoin and 5-fluorouracil 5% cream.…”
Section: Discussionmentioning
confidence: 99%
“…Various approaches have been reported to address these issues associated with retinoid therapy of PMOLs, including the use of newer synthetic retinoid analogues (for example, fenretinide: [9] and studies focussed on the identification of biomarkers, which may predict retinoid sensitivity [9,[19][20][21][22]. A further possible approach has been used in other cancers: the addition of de-methylating agents to retinoids treatment.…”
Section: Introductionmentioning
confidence: 99%